ІНТЕГРАЦІЯ ІНВАЛІДІВ ПО ЗОРУ ДО - МІНАКОВА, К.В (Гуманітарний журнал, 2011)
В статье рассматривается процесс организации сотрудничествамузеев Днепропетровской области с инвалидами по зрению в русле мировойпрактики и с цельювоплощения положений Конвенции о правах инвалидов.

The article deals with the implementation process of cooperation ofmuseums inDnipropetrovsk region and peoplewithvisual disabilities in linewith globalpractices and to implementthe Convention on theRights of Persons withDisabilities
Keywords: музей и инвалиды; социальная адаптация; новейшие музейные технологии; museumand the people with disability; modern technologies in themuseum.